(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Vitamin D is crucial for calcium, phosphate homeostasis and mineralization of the skeleton, particularly through growth time developments. Vitamin D deficiency lead to rickets in children and osteoporosis in adult. The activity of vitamin D receptors (VDR) are responsible for the vitamin D so that the single nucleotide polymorphism was detected using BsmI. Material and methods: In this study, the vitamin D3 level were measured using enzyme-linked sorbent assay (ELISA) technique, followed by detection of the polymorphism VDR- BsmI gene using PCR and BsmI restriction enzyme assay (PCR RFLP). Results: Vitamin D, alkaline phosphate and others biochemical were performed in 50 patients beta thalassemia were divided into 25 males and same number females. The biochemical results demonstrated no significant difference p<0.05 between males and females according gender, whereas showed high significant serum calcium p value 0.048 according body mass index. We using RFLP-PCR technique to amplify VDR gene BsmI, DNA ladder molecular weight was 1000-2500 base pair and BsmI digestion showing predicted product in 823 to 175 pb in all lane. Conclusions: BsmI digestion was showing heterozygous mutant (Bb) and homozygous (BB). These result gene polymorphism VDR BsmI effected on vitamin D levels and related with bone diseases and process metabolism.